2001
DOI: 10.1038/35077011
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an ACh-binding protein reveals the ligand-binding domain of nicotinic receptors

Abstract: Pentameric ligand gated ion-channels, or Cys-loop receptors, mediate rapid chemical transmission of signals. This superfamily of allosteric transmembrane proteins includes the nicotinic acetylcholine (nAChR), serotonin 5-HT3, gamma-aminobutyric-acid (GABAA and GABAC) and glycine receptors. Biochemical and electrophysiological information on the prototypic nAChRs is abundant but structural data at atomic resolution have been missing. Here we present the crystal structure of molluscan acetylcholine-binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

59
1,967
1
39

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,707 publications
(2,066 citation statements)
references
References 47 publications
59
1,967
1
39
Order By: Relevance
“…Nevertheless, a5 di ers from typical a subunits in the domains thought to be important for agonist binding, lacking, for instance, Tyr93 and Tyr190. In nicotinic ACh receptors (nAChR) typical a subunits contribute either the whole of the agonist binding domain (Unwin, 2001) or the subsite for the ACh ester moiety (Karlin & Akabas, 1995;Brejc et al, 2001). A typical neuronal a subunit (a2, a3 or a4) will form functional nAChRs when expressed heterologously together with a typical b subunit (b2 or b4; Lindstrom, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a5 di ers from typical a subunits in the domains thought to be important for agonist binding, lacking, for instance, Tyr93 and Tyr190. In nicotinic ACh receptors (nAChR) typical a subunits contribute either the whole of the agonist binding domain (Unwin, 2001) or the subsite for the ACh ester moiety (Karlin & Akabas, 1995;Brejc et al, 2001). A typical neuronal a subunit (a2, a3 or a4) will form functional nAChRs when expressed heterologously together with a typical b subunit (b2 or b4; Lindstrom, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The initial crystal structure showed the amine containing buffer, HEPES at ~100mM concentration, to occupy the agonist site [6]. Crystallization in the presence of polyethylene glycol shows low occupation of the cryoprotectant in the agonist site and radial extension of the C loop from the core backbone of the molecule [11] (Fig.…”
Section: Crystal Structures Of Competitive Agonists and Antagonistsmentioning
confidence: 99%
“…Several structures of agonist (epibatidine, nicotine, lobeline, carbamylcholine) and antagonist (α-conotoxin, methyllycaconitine, α-bungarotoxin) bound to AChBP have been reported [6,[9][10][11][12], and other structures have been resolved at high resolution or are under study. Hence, one now has a fairly comprehensive perspective on structures of the AChBP complexes.…”
Section: Crystal Structures Of Competitive Agonists and Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that the nicotinic binding site is located at the centre of the extracellular domain of the receptor and lies at the interface between  and β subunits, which are known as the principal (P) and complementary (C) components, respectively [48][49][50]. Several residue stretches referred to as loops A, B and C in the  subunit, and D, E and F in the β subunit shape the binding site (in the following the symbols "" and "β" will be used before the residue to indicate the subunit it belongs to, and the numbering refers to the 4 and β2 subunits in rat).…”
Section: Binding Mode Of Mdmamentioning
confidence: 99%